Enhanced thermoelectric properties of 2H–MoS2 thin film by tuning post sulfurization temperature. Issue 13 (1st July 2022) - Ashfaq, Arslan; Tahir, Sofia; Rehman, Ubaid ur; Ali, Adnan; Mehmood, Khalid; Ashfaq, Fareeha; Ahmad, Waqas; Khan, Khushi Muhammad; Haneef, M.; Mushtaq, H.M. Shammas; Amin, Nasir; Saeed, Rabia; et al.
Abstract: Two-dimensional transition metal dichalcogenide semiconductors (TMDCs) like MoS2 are becoming more popular as thermoelectric materials because they are abundant, nontoxic, and have good performance. In the study, the MoS2 thin films have prepared by the sputtering and post-sulfurization process at various temperatures 450 °C, 550 °C, 650 °C, and 750 °C. The XRD data exhibits the formation of the 2H phase of MoS2 thin film with (002), (004), and (006) planes. The Raman spectroscopy has confirmed the 2H–MoS2 thin films with 2LA (M), A1g, E2g, and Eg vibrational modes. The SEM images have shown the thin MoS2 flakes. The Seebeck and electrical conductivity data indicated an enhancement in Seebeck coefficient and electrical conductivity from 20 to 31 μV/ ° C and 26–53 S/m, respectively, as the post sulfurization temperature increased from 450 °C to 750 °C. The enhancement of the Seebeck coefficient and electrical conductivity have been linked to the perfection of the 2H phase of MoS2 film. The improved crystal structure has increased carrier mobility, leading to a high power factor of the 5.09 μWm −1 C −2 .